Marketing opportunities of local products in the catchment area of Csíkszereda town - Péter, Emőke-Katalin (Applied Studies in Agribusiness and Commerce, 2020)
Agriculture plays an outstanding role in Romania, since there are nearly three and a half million small farms operating in the country, accounting for almost 90% of the total number of farms, and scarcely more than 32% of the available farm land is cultivated by 35% of the population. In the settlements found in the catchment area of Csíkszereda, the majority of farms consist of family farms smaller than 5 hectares. The marketing of good quality products made from local raw material by traditional methods contributes to the sustenance of the family farms. Researches show that as a result of the education of the farmers on a local level more and more processed products appear in the markets of Csíkszereda town. Farmers involved in the local market intend to expand their farms on the long run. The respondents consider that “a piece of land can be sold only once”, that is why the sustenance of the farm became the main goal of multi-generational effort. Younger farmers are usually more educated and more open to innovation. The vast majority of farmers under 45 find it important to market their products through rural tourism and they are also more eager to join producer groups. Young farmers need to merge traditional methods and knowledge inherited from previous generations with modern opportunities and methods that facilitate production and marketing. Knowledge gained this way makes it possible for small farms to market their products through short supply chains. JEL code: Q12,Q13